2006
DOI: 10.1001/jama.295.2.180
|View full text |Cite
|
Sign up to set email alerts
|

International Prevalence, Recognition, and Treatment of Cardiovascular Risk Factors in Outpatients With Atherothrombosis

Abstract: This large, international, contemporary database shows that classic cardiovascular risk factors are consistent and common but are largely undertreated and undercontrolled in many regions of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
932
10
124

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,431 publications
(1,118 citation statements)
references
References 30 publications
52
932
10
124
Order By: Relevance
“…These higher event rates may be driven by a large proportion of patients with CAD (90%). Interestingly, these data are consistent with findings from the REACH registry, which has a large percentage of patients with PAD combined with CAD and is associated with high mortality rates 22. Therefore, accurate risk prediction and identification for underlying pathophysiology in patients with PAD is critically meaningful.…”
Section: Discussionsupporting
confidence: 85%
“…These higher event rates may be driven by a large proportion of patients with CAD (90%). Interestingly, these data are consistent with findings from the REACH registry, which has a large percentage of patients with PAD combined with CAD and is associated with high mortality rates 22. Therefore, accurate risk prediction and identification for underlying pathophysiology in patients with PAD is critically meaningful.…”
Section: Discussionsupporting
confidence: 85%
“…Study details have been described elsewhere 6, 7, 20. In the present study, we included patients with stable clinical coronary artery disease, cerebrovascular disease and/or peripheral artery disease from both cohorts.…”
Section: Methodsmentioning
confidence: 99%
“…In particular with the emergence of novel therapeutic options such as proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors, novel anticoagulants, or anti‐inflammatory agents, tools to predict recurrent cardiovascular events are needed 2, 3. Recently, 2 risk scores have been developed for the prediction of recurrent cardiovascular events based on the observational REACH (Reduction of Atherothrombosis for Continued Health) and SMART (Secondary Manifestations of Arterial Disease) cohort studies 4, 5, 6, 7, 8, 9. These scores estimate the 20‐month (REACH) and 10‐year (SMART) risk of recurrent major cardiovascular events in patients with established cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported underutilization of established risk‐reduction therapies such as statins for peripheral artery disease relative to coronary artery disease,6, 7, 8 which may lead to poor cardiovascular and limb outcomes 9. Nevertheless, few data exist on the utilization of statin therapy among patients with carotid artery disease.…”
Section: Introductionmentioning
confidence: 99%